Cyclic Growth and Global Stability of Economic Dynamics of Kaldor Type in Two Dimensions - Aka Fulgence Nindjin; Albin Tetchi N’Guessan; Hypolithe Okou; Kessé Thiban Tia (International Journal of Differential Equations)
This article proposes nonlinear economic dynamics continuous in two dimensions of Kaldor type, the saving rate and the investment rate, which are functions of ecological origin verifying the nonwasting properties of the resources and economic assumption of Kaldor. The important results of this study contain the notions of bounded solutions, the existence of an attractive set, local and global stability of equilibrium, the system permanence, and the existence of a limit cycle.